DAMPAK NEGATIF KEBIJAKAN HUKUM TRANSAKSI SIPIL UNI EMIRAT ARAB (UEA) TERHADAP PEKERJA MIGRAN INDONESIA (PMI) - Syakara, Muhammad Rifqi; Pahlawan, Indra (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
The rapid development of digital financial technology and the adoption of crypto assets in the global economic system have begun to influence various sectors, including their use as payment methods for migrant workers. The United Arab Emirates (UAE), through the Virtual Asset Regulatory Authority (VARA), is one of the countries that has progressively regulated the use of crypto assets in civil transactions, including wage payments for foreign workers. In contrast, Indonesia maintains a conservative approach by classifying crypto as a commodity under the supervision of Bappebti, without a specific framework governing its use in the context of migrant labor. This study employs a qualitative approach using literature review and policy document analysis issued by relevant authorities in both the UAE and Indonesia. The liberal economic theory and the nation-state concept are used to explain how states respond to digital transformation within civil transaction laws and its implications for the protection of migrant workers’ rights. The findings reveal significant negative impacts on Indonesian migrant workers in the UAE, including wage instability, low digital literacy, and Indonesia’s limited legal capacity to protect its workers from crypto-based wage practices. Keywords: Crypto Assets, Civil Transaction Law, Civil Transactions, Migrant Workers, Virtual Asset Regulatory Authority.